Bioheat Transfer Equation in Living Tissue and Some Applications - Gurung, Dil Bahadur (The Nepali Mathematical Sciences Report, 2018)
Mathematical formulation for heat transfer in living tissue is different than an inert material, and is a current growing research interest area for many researchers due to its wide applications in many medical therapies and physiological studies. This interest stems from the rapid advancement of computational technology and advanced numerical mathematical techniques. The paper focuses on review on basic formulations of bio-heat equation proposed so far by several authors in the living tissue and its some applications.